RETRACTED: Uzbek mahalla: History and modern peculiarites of multiethnic, confessional neighborhoods - Kamilov Abdusalim; Tishabayeva Lola; Rakhimov Ilkhomjon; Ergashov Umidjon; Kadirova Dildora (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001